Sex Hormones, Exercise and Women : Scientific and Clinical Aspects - Hackney, Anthony C. (Springer International Publishing : Imprint: Springer, 2017)
It is well-established, through extensive peer-reviewed published research, that physical activity and exercise training can impact the reproductive endocrine system of women. This ground-breaking, comprehensive title presents a range of unique insights into the opposite question: how the reproductive endocrine system of women affects their exercise ability. More precisely, the thematic question explored in this work is: if exercise affects reproductive hormones, conversely then could the reproductive hormones have physiological effects unrelated to reproduction that influence the capacity of women to exercise? In exploring this question, the goal is to better understand the unique physiology of women and whether female sex hormones might account for some of the variance in physiological performance between amenorrheic and eumenorrheic women, and within women across the age span as they experience menarche to menopause. Sex Hormones, Exercise and Women: Scientific and Clinical Aspects synthesizes the research by exploring the physiology and psychology behind these occurrences. This novel title will not only be of interest to researchers, exercise scientists, graduate students, and clinicians; it will also serve as a source of valuable information for female athletes and their trainers in the context of preparing for competitions.
Keywords: Medicine.; Gynecology.; Cardiology.; Endocrinology.; Sports medicine.; elektronické knihy; electronic books